Optimal Inspection Policy for Scheduled Maintenance of Aging Systems - Jin, Lu; Yamamoto, Watalu (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
This research provides a flexible inspection policy in which the interval between the current and next inspection is determined on the basis of the current information about the system. A non-stationary partially observed Markov decision process model was used to formulate a decision-making problem for an aging system with imperfect inspection, and the optimal inspection policy which minimizes a long-run expected cost over an infinite time horizon was analytically investigated. Several structural properties of the optimal expected cost function were obtained that establish the existence of an optimal policy in which there is at most one transition from keep-operating to replacement with respect to both the system’s deterioration and age under certain conditions. A monotone property of the inspection interval was identified. Furthermore, the obtained conditions were discussed and a numerical calculation was provided to show how to obtain the optimal inspection policy.